CLINICAL GUIDELINE FOR THE TREATMENT OF DIABETIC NEPHROPATHY - R. A. Nadeeva; O. N. Sigitova (Архивъ внутренней медицины)
Due to the high prevalence of diabetes the annual increase of the number of patients with diabetic nephropathy is evidenced. The progressive course of this sequellae and a high percentage of end-stage kidney disease requires a clear approach of early diagnosis, the development of methods of prevention and early treatment from the perspective of evidence-based medicine. This review provides recommendations on glucose-lowering treatment, monitoring of blood pressure and proteinuria, hyperlipidemia. Defi ned individual targets of the correction of hyperglycaemia, depending on the level of albuminuria excretion and the severity of the patient. Indicated the possibilities of applications of certain antidiabetic drugs, depending on the level of glomerular fi ltration rate. Drugs of the fi rst and second line are marked for the selection of antihypertensive treatment. Showed the possible ways to reduce the level of albuminuria. Presented recommendations for the management of patients, depending on the stage of nephropathy.